KONSELINNG INDIVIDU UNTUK MENGATASI KESULITAN DALAM MENGAMBIL KEPUTUSAN KARIR DENGAN PENDEKATAN TRAIT AND FACTOR - Imam, Achmad Shokhibul; Sucipto, Sucipto; Santoso, Santoso (Universitas Muria Kudus, 2023)
This study aims to: 1) Knowing the factors that cause difficulties in determining career decisions in students of SMK Negeri 1 Kudus. 2) Knowing the effectiveness of implementing the trait and factor approach to overcome difficulties in determining career decisions for students of SMK Negeri 1 Kudus.The difficulty in determining is that it is difficult for the counselee to determine and process the selection of alternative ways in a career that is carried out intentionally, seriously, and has been considered according to what the counselee wants in order to create career satisfaction. For this vocational students, it is difficult to determine a career, namely making job applications for work or making their own business according to their majors, continuing their studies to college, these things must be thought carefully because later will affect career satisfaction in the future. In dealing with students who are still difficult to make career decisions, the researchers apply trait and factor counseling because this counseling emphasizes the compatibility between education and position. In this study, the technique of providing trait and factor counseling assistance was adjusted to the individual problems of each, for this there is no standard technique that applies to both counselees. All techniques must be determined specifically according to the problem felt by the counselee. This type of research uses a type of qualitative research that is arranged in a case study method conducted at SMK Negeri 1 Kudus. The subjects studied were DSF, CSM, students of class XII TBG 2 and 3 for the academic year 2021/2022.